Advancing Local Economy through Good Governance - Nyalungu, Jey; Mbona, Sizwe; Ogunsola, Sijuwade (Acta Universitatis Danubius. Œconomica, 2025)
Objectives: the aim of this study is to explore the role of governance in fostering economic growth and development at local municipalities. Good governance promotes investor confidence, attracts businesses, and facilitate entrepreneurship. The study further seeks to appreciate the dynamics of local economies, their significance to economic growth, and challenges, while proposing strategies for sustainability. Prior work: this paper is premised on the existing theory on corporate governance. Approach: the current study used a self-administered questionnaire, with structured closed-ended questions on a Likert scale to collect data from the employees of uMngeni local municipality. A sample of 106 respondents was obtained. Data was analyzed using SPSS, version 29.20. Results: the findings of this study showed that systems within the municipality have a statistically significant strong positive correlation with service delivery. Implications: the current governance model is not sustainable to stimulate economic growth and development. Given the complexity of service delivery deficiencies across local governments, there is a persistent need to exercise good governance in municipalities. The local government should concern itself with the setting up of an appropriate corporate governance system that will lead to municipal efficiency.